Breastfeeding Barriers and Support in a Rural Setting. Issue 2 (March 2016) - Goodman, Laurel R.; Majee, Wilson; Olsberg, Joshua E.; Jefferson, Urmeka T.
Abstract: Purpose: Although various breastfeeding interventions have proven effective in increasing breastfeeding initiation and duration, there has been less success in rural areas. This article describes breastfeeding barriers and support in a rural setting. Study Design and Methods: A community needs assessment was conducted with a sample of healthcare providers and breastfeeding mothers in a rural area of Missouri. In-depth interviews with 10 healthcare providers and 3 breastfeeding mothers and a focus group of 10 mothers who were breastfeeding or had recently breastfed were conducted. Interview and focus group questions were designed to capture a holistic perspective of breastfeeding issues. Results: Gaps in hospital and community breastfeeding support were observed in the emerging themes: lack of realistic information about the breastfeeding experience, breastfeeding time constraint, and lack of continued support. Clinical Implications: From a community practice perspective, gaps in breastfeeding support illustrate an essential need for collective engagement of local stakeholders as the cornerstone to implement effective breastfeeding interventions. Abstract : A community assessment in a rural area of Missouri was conducted to identify challenges to successful breasfeeding. Breastfeeding women and healthcare providers offer their insights on current realities and what would be needed to improve breastfeeding rates.